User-Experience-Oriented Fuzzy Logic Controller for Adaptive Streaming. (8th February 2018) - Hou, Yonghong; Xue, Lin; Li, Shuo; Xing, Jiaming
Abstract: HyperText Transfer Protocol (HTTP) streaming has been widely used for multimedia delivery nowadays. To adapt to the heterogeneous networks and different terminals, the rate adaptation controller is developed as the core part of the video transmission system. In this paper, a three-input fuzzy controller is designed to enhance the users' quality-of-experience (QoE) on watching online video. The introduction of fuzzy logic is able to solve the problem that there is no rule to set the reasonable buffer thresholds in the buffer-based adaptation controller. The normalized throughput, the buffer level and the buffer variation are used as the inputs of the controller to minimize the inevitable mismatch caused by limited bitrate levels and to help the system converge to a stable state. The proposed controller is compared with three other controllers under three simulation network conditions and an actual vehicle condition. A QoE model is simultaneously used to get intuitive and comprehensive results. The results show that among all the four conditions, the proposed controller can provide better QoE than other algorithms.